Labor on the Fringes of Empire - Stanziani, Alessandro. author. aut Link
XIII, 334 p. 7 illus.
Keywords: After the abolition of slavery in the Indian Ocean and Africa, the world of labor remained unequal, exploitative, and violent, straddling a fine line between freedom and unfreedom. This book explains why. Unseating the Atlantic paradigm of bondage and drawing from a rich array of colonial, estate, plantation and judicial archives, Alessandro Stanziani investigates the evolution of labor relationships on the Indian subcontinent, the Indian Ocean and Africa, with case studies on Assam, the Mascarene Islands and the French Congo. He finds surprising relationships between African and Indian abolition movements and European labor practices, inviting readers to think in terms of trans-oceanic connections rather than simple oppositions. Above all, he considers how the meaning and practices of freedom in the colonial world differed profoundly from those in the mainland. Arguing for a multi-centered view of imperial dynamics, Labor on the Fringes of Empire is a pioneering global history of nineteenth-century labor.